Association Between Tobacco Dependence And Dental Caries - AKMAL, NUR LIYANA HANNAH BINTI IZHAM; BALASUBRAMANIAM, ARTHI; DURAISAMY, REVATHI (The journal of contemporary issues in business and government, 2021)
Tobacco is considered as the greatest disease-inducing substance globally associated with prevalent addictive habits and harmful influence on the behaviour of an individual and public health. Several studies have discussed the association between dental caries and tobacco consumption particularly in terms of smoking habits. The aim of this study is to evaluate the effects of smoking and chewing tobacco habits and its dependence on prevalence of dental caries. A retrospective study was conducted using case records of University hospital. Descriptive statistics was done to present the distribution of DMFT scores. Chi-square association was done to find the association. A total of 941 consecutive case records with registered DMFT index scores of age above 18 years was retrieved and analysed. All 941 consecutive case records were evaluated in this study. Patients of age group 21-30 years were predominantly seen with tobacco dependence (32.3%) when compared to the other age groups. Tobacco dependence was high with males (97.46%) when compared to females (2.55%). Most of the patients with tobacco dependence had DMFT scores of 0-5 (67.47%). A statistically significant association exists between tobacco dependence with age and gender (p<0.05) but no association with dental caries (p>0.05). Within the limits of the present study, tobacco dependence is associated with age and gender where males of age group 21-30 years show higher tobacco dependence. However, tobacco dependence and dental caries are not associated with more prevalence of dental caries among individuals with very low tobacco dependence.